Neoclassical Realism Theory in studying Military Interventions: Developing a Poliheuristic Approach - Bivainis, Andrius (Politologija, 2018)
[full article and abstract in Lithuanian; abstract in English] The precedents of military interventional decisions by Western countries in the Middle East have been an uneasy topic with vague, long-term strategic objectives and increased questionable attitudes among domestic audiences. This article questions whether these precedents require an updated methodological approach. The aim of this article is to adopt a poliheuristic methodology as an analytic instrument for examining military intervention precedents in the Middle East. This article suggests an analytical solution based on a poliheuristic research methodology, previously defined by Alex Mintz and applied in foreign policy research. This article highlights the need to adopt the methodology to military interventional decisions with an inclusion of additional decision dimensions. The first part of the article reveals a synthesis of the theoretical notions of neoclassical realism. These notions are correlated with the elements of poliheuristic methodology. This path of analysis, applied to theoretical notions and the adopted poliheuristic methodology, reveals additional variables that have a transdimensional role in the military intervention decision process. The following are the variables that influence the cognitive and rational elements of the poliheuristic methodology: the competing dominance of normative or operational ideas, interventional experience and shifting notions of strategic culture. The final part of the article offers an empirical study that illustrates how the suggested poliheuristic methodology is to be applied. The case pays attention to the decision of Barack Obama’s administration in 2013 to not escalate its military intervention into the Syrian conflict. Considerations of the Syrian case are also correlated to the previous multinational military campaign in Libya.